2021
DOI: 10.3390/polym13111714
|View full text |Cite
|
Sign up to set email alerts
|

Non-Covalent Interactions on Polymer-Graphene Nanocomposites and Their Effects on the Electrical Conductivity

Abstract: It is well known that a small number of graphene nanoparticles embedded in polymers enhance the electrical conductivity; the polymer changes from being an insulator to a conductor. The graphene nanoparticles induce several quantum effects, non-covalent interactions, so the percolation threshold is accelerated. We studied five of the most widely used polymers embedded with graphene nanoparticles: polystyrene, polyethylene-terephthalate, polyether-ketone, polypropylene, and polyurethane. The polymers with aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…4c, it is observed that deformations are induced due to the rearrangement of the organic groups in the Eu III environment, whose intermolecular interactions generate new forces to maintain the original equilibrium state with its new conformation. 69 These forces are often seen as internal stresses, which possess a short action radius (distance between the maximum and minimum heights near the polymer), leading to several fine-tunings in the energy of the occupied and unoccupied states, influencing the band gap of the phosphor. 70,71…”
Section: Resultsmentioning
confidence: 99%
“…4c, it is observed that deformations are induced due to the rearrangement of the organic groups in the Eu III environment, whose intermolecular interactions generate new forces to maintain the original equilibrium state with its new conformation. 69 These forces are often seen as internal stresses, which possess a short action radius (distance between the maximum and minimum heights near the polymer), leading to several fine-tunings in the energy of the occupied and unoccupied states, influencing the band gap of the phosphor. 70,71…”
Section: Resultsmentioning
confidence: 99%
“…π-π interaction, a type of Van der Waals force, is known to hold graphene sheets together at a distance of 0.335 nm [35,36]. Given that polystyrene has a mer unit containing an aromatic ring, a mechanism of interaction with graphene through π-π and CH-π interactions is possible [37]. However, the density in aromatic rings in PS is less than in graphene given that they are more spaced out by the carbon main chain of the macromolecule.…”
Section: Morphology Of Graphene Compositesmentioning
confidence: 99%
“…In that way the resulted polymer-graphene material acquires higher solubility, very good conductivity and offers much larger area that can accommodate much more metal nanoparticles, lacking any aggregation trends. Moreover, the as-resulted pasta can be applied directly to a glassy carbon electrode for further experimental investigation [ 85 , 86 ].…”
Section: Graphene-based Nanomaterials For Glucose Electrochemical Sensorsmentioning
confidence: 99%
“…Taking as an example the work of Deshmukh et al [ 89 ], the N-atoms of PANI seems to engage with the metal nanoparticles, enabling electronic interaction and in combination with rGO large surface area, enhance electron transfer and so glucose electrooxidation reaction process. Furthermore, according to Apátiga et al [ 86 ] work, the polymers with aromatic ring structure, when they are dispersed into graphene solution, due to the π-π graphene stacking, the so long-term dispersion interactions prevail. On the contrary when the polymers’ structure is linear, prevail the short-range dispersion interactions, that are attributed to the CH-π stacking.…”
Section: Graphene-based Nanomaterials For Glucose Electrochemical Sensorsmentioning
confidence: 99%